Hungarian Monitoring, 26 March 1988 . [Magyar rádiófigyelő], 1988. március 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Uzbek-Azerbaijan conflict - Disturbances in Latvia Domestic Affairs: - Péter Medgyessy discusses Hungarian-Austrian relations in Vienna - President of the World Council for Peace in Budapest - Central Committee deliberations - Young Communist League (KISZ) Central Committee in session - Saint Stephen Memorial Committee in session - Is the Pető Institute in danger? - Did Radio Free Europe help incite the religious demonstration in Bratislava? Külpolitika: - Üzbég-azerbajdzsáni konfliktus - Zavargások Lettországban Belpolitika: - Medgyessy Péter a magyar-osztrák kapcsolatokról tárgyal Bécsben - Budapesten a Béke Világtanács elnöke - KB tanácskozás - KISZ KB ülés - Szent István Emlékbizottság ülése - Veszélyben a Pető Intézet? - A SZER is uszította a pozsonyi vallási tüntetést?